Faktor – Faktor Yang Dapat Mempengaruhi Kecenderungan Kecurangan Akuntansi - Dewi, Sinta Laksmi; Indraswarawati, Sang Ayu Putu Arie; Satriya, I Wayan Budi (UNHI Press, 2025)
The tendency of accounting fraud is a form of misrepresentation or omission of amounts in the financial reporting process done intentionally to deceive the users of the reports. Accounting fraud also describe misrepresentation that arises due to improper application of accounting principles related to asset management, which results in non-compliance with Indonesian Financial Accounting Standards (PABU). The studi aim’s to determine the influence of the Implementation of Good Corporate Goverrnance and the Effectiivenes’s of Internal Control on the tendency of accounting fraud in Village Credit Institutions. Research was conductted on 8 Viillage Credit Institutiions in the Kuta Selatan District. Size for sampel on this study is 66 respondents selected usiing non-probabiility sampling methods. The analysiis technique used for this study is mulltiple linear regression. Result for this study the implementation of good corporate governance has a negative and signifiicant effect on the tendenciy of accounting fraud, and the effectiveness of internal control also has a negative and signifiicant effect on the tendency of accounting fraud.